miR-543 impairs breast cancer cell phenotypes by targeting and suppressing ubiquitin-conjugating enzyme E2T (UBE2T) - Li Li (Taylor & Francis Group, 2021)
Breast cancer, with high morbidity worldwide, is a threat to the life of women. MiR-543 was identified as playing an active part in the development of breast cancer involving multiple molecules. The goal of this study was to explore the molecular mechanisms of the involvement of miR-543 in the development of breast cancer. Quantitative real-time PCR (qRT-PCR) or western blotting was used to detect mRNA or protein expression. Cell counting kit-8 (CCK-8), and the 5-bromo-2ʹ-deoxyuridine (BrdU), wound healing, and Transwell assays were the main experimental procedures. Furthermore, subcutaneous tumor formation experiments were conducted to detect the function of miR-543 in breast cancer development in vivo. The match of miR-543 and ubiquitin-conjugating enzyme E2T (UBE2T) was detected through a dual-luciferase reporter experiment and RNA pull-down assay. Based on these results, miR-543 exhibited reduced expression in breast cancer tissues and cell lines, whereas UBE2T exhibited high levels. Furthermore, miR-543 directly targeted UBE2T, and a negative correlation between miR-543 and UBE2T was also observed in breast cancer tissues. Moreover, miR-543 overexpression led to inhibition of viability, proliferation, migration, and invasion of breast cancer. Furthermore, miR-543 overexpression undermined the UBE2T promotional effect by inhibiting ERK/MAPK pathway activity in breast cancer cells. Our study revealed that miR-543 impaired breast cancer progression by targeting UBE2T and downregulating UBE2T expression through the ERK/MAPK pathway, which suggested that miR-543 and UBE2T might serve as promising therapeutic gene targets for breast cancer in clinical application.